Co-operative schools: democratic values, networks and leadership. Issue 11 (2nd November 2019) - Woodin, Tom
ABSTRACT: For over a decade, co-operative schools have struck a note of discord within the highly orchestrated context of English education policy. They encapsulate an old set of ideas but re-articulate them for new times by engaging with educational frameworks which are locked into the so-called global education reform movement (GERM) based upon on standards, standardisation, a mixture of centralised and devolved accountabilities, leadership, testing and accountability. Yet co-operative schools ostensibly aim to embed a set of wide-ranging values and principles: equality, equity, democracy, self-help, self-responsibility and solidarity as well as the principles of education, democratic control and community ownership, all of which echo the history of labour movements. The co-operative legal model not only adheres to co-operative values and principles but necessitates stakeholder involvement in the governance of schools: pupils, staff, parents, community and, potentially, alumni are all expected to play a role. These are compared to David Hargreaves' ideas about a 'self-improving school system'. I analyse the emergence of the co-operative network and the reasons for its dramatic growth alongside the complex problems it faced. In turn, these help us to understand the possibilities and contradictions inherent in attempts to build inclusive and democratic educational networks.